ANALISIS FIQH ASNAF FI SABILILLAH DAN IMPLEMENTASINYA PADA BADAN ZAKAT NASIONAL - Aang Gunaepi; Didin Hafidhuddin; Irfan Syauqi Beik (Kasaba, 2019)
This study describe fiqh one of all asnaf on zakat, there are fi sabilillah and how imply at BAZNAS. This research uses library research and field research as complement with qualitative approach. Fi sabilillah have same means that jihad. Fi sabilillah dalam BAZNAS imply to empowerment of mustahik with scholarship from elementary until higher education.